Violência urbana como experiência coletiva e como arte em Manual Prático do Ódio, de Ferréz - Alves, Rhegysmere Myrian Rondon (2016)
This study consists of the analysis of the literary trajectory of the Brazilian writer Reginaldo Ferreira da Silva (1975 -) - better known as Ferréz - whose narratives are centered on the fictionalization of the Brazilian outskirts. From these fictional constructions we propose to think in the singular way in which the author launches himself to the composition of a look at the daily life of the outskirts that surround him, the Capão Redondo. Ferréz, in the articulation of his literary work with his own experience of living in peripheral space, launches to the discussion of literature the debate about the conditions of his production today, the place assumed by the author and the kind of bond that his work establishes with the community. His literary material, especially the first two published novels, Capão pecado (2000) and Manual prático do ódio (2003), the book of tales the ricos também morrem (2015) and the tale Pensamentos de um correria (2007) were the instruments from which we allow ourselves to talk about this reading pact that admits a writing that is near to narrated reality. The admission that this writing maintains a real content of verisimilitude, led our approximations of the relations between testimony and marginal writing in the works of the author. And it made possible that the study of the testimony in its relation with the modalities of the writings of the "I" here, became important in our analyzes, mainly using theoretical references about autobiography and self-writing. The notions of autobiography and autobiographical space will help us to think about the existence of characteristics that in the novels make possible the construction of an autobiographical reading pact.